Protein Kinases Mediate Anti-Inflammatory Effects of Cannabidiol and Estradiol Against High Glucose in Cardiac Sodium Channels - Fouda, Mohamed A.; Ruben, Peter C. (Frontiers in Pharmacology, 2021)
Background. Cardiovascular anomalies are predisposing factors for diabetes-induced morbidity and mortality. Recently, we showed that high glucose induces changes in the biophysical properties of the cardiac voltage-gated sodium channel (Nav1.5) that could be strongly correlated to diabetes-induced arrhythmia. However, the mechanisms underlying hyperglycemia-induced inflammation, and how inflammation provokes cardiac arrhythmia, are not well understood. We hypothesized that inflammation could mediate the high glucose-induced biophyscial changes on Nav1.5 through protein phosphorylation by protein kinases A and C. We also hypothesized that this signaling pathway is, at least partly, involved in the cardiprotective effects of cannabidiol (CBD) and estradiol (E2). Methods and results. To test these ideas, we used Chinese hamster ovarian (CHO) cells transiently co-transfected with cDNA encoding human Nav1.5 α-subunit under control, a cocktail of inflammatory mediators or 100 mM glucose conditions (for 24 hours). We used electrophysiological experiments and action potential modelling. Inflammatory mediators, similar to 100 mM glucose, right shifted the voltage dependence of conductance and steady-state fast inactivation and increased persistent current leading to computational prolongation of action potential (hyperexcitability) which could result in long QT3 arrhythmia. We also used human cardiomyocytes derived from inducible pluripotent stem cells (iPSC-CMs) as a physiologically relevant system, and they replicated the effects produced by inflammatory mediators observed in CHO cells. In addition, activators of PK-A or PK-C replicated the inflammation-induced gating changes of Nav1.5. Inhibitors of PK-A or PK-C, CBD or E2 mitigated all the potentially deleterious effects provoked by high glucose/inflammation. Conclusions. These findings suggest that PK-A and PK-C may mediate the anti-inflammatory effects of CBD and E2 against high glucose-induced arrhythmia. CBD, via Nav1.5, may be a cardioprotective therapeutic approach in diabetic postmenopausal population.